Transforming an IORT Linac Into a FLASH Research Machine: Procedure and Dosimetric Characterization - Felici, Giuseppe; Barca, Patrizio; Barone, Salvatore; Bortoli, Eleonora; Borgheresi, Rita; De Stefano, Silvia; Di Francesco, Massimo; Grasso, Luigi; Linsalata, Stefania; Marfisi, Daniela; Pacitti, Matteo; Di Martino, Fabio (Frontiers in Physics, 2020)
Since Favaudon’s paper of 2014, there has been an increasing interest in FLASH radiotherapy. The FLASH modality could represent a breakthrough in radiation oncology; nevertheless, it brings new scientific and technological challenges. Currently, one of the main limits the scientific community has to cope with is the lack of a common technological platform to experiment with. Considering this framework, the possibility of readapting existing linac platforms to produce a FLASH beam is particularly attractive and different attempts have been already made. The purpose of this article is to illustrate how it is possible to transform a dedicated Intra Operative Radio Therapy (IORT) mobile linac into a FLASH research machine. Compared to the modification required by a standard medical linac, such transformation is easier, does not affect the machine settings and can be rapidly performed by the final user. NOVAC 7 is an IORT linac which can reach a maximum dose-per-pulse up to 13 cGy/pulse (average dose rate 39 Gy/min); such dose rate can be significantly increased by modifying the collimation system. Four different Source Surface Distance (SSD) can be obtained: -Clinical reference configuration; -Upper applicator only (SSD 50 cm); -Monitor chambers housing only (SSD 7 cm); -Dismounted monitor chambers (SSD 1.6 cm). The fourth configuration allows reaching values of dose-per-pulse up to around 18 Gy/pulse and dose rates up to around 500 Gy/s, at a Pulse Repetition Frequency (PRF) of 30 Hz. The other three configurations can be obtained without using any tool and without changing NOVAC settings, until reaching a FLASH dose rate in the third configuration. For FLASH configurations, relative and absolute dosimetric characterization of the beam were performed using radiochromic films EBT3. NOVAC7 transformed in FLASH mode can be used both for dosimetric testing and characterization of detectors and for radiobiological studies on cells and organoids, offering a wide range of dose-per-pulse, from 3 cGy/pulse up to 18 Gy/pulse; dose rates correspondingly change from 3 cGy/s up to 540 Gy/s.